DGAT2 Inhibition Potentiates Lipid Droplet Formation To Reduce Cytotoxicity in APOL1 Kidney Risk Variants. Issue 5 (May 2022) - Chun, Justin; Riella, Cristian V.; Chung, Hyunjae; Shah, Shrijal S.; Wang, Minxian; Magraner, Jose M.; Ribas, Guilherme T.; Ribas, Hennrique T.; Zhang, Jia-Yue; Alper, Seth. L.; Friedman, David J.; Pollak, Martin R.
Significance Statement: Variants G1 and G2 of the gene encoding apolipoprotein L1 (APOL1) are associated with increased risk of kidney disease in certain populations. In previous work, the authors demonstrated that recruitment of these variants from the endoplasmic reticulum to lipid droplets is associated with reduced cytotoxicity in podocytes. In this study, they confirm differences in lipid droplet distribution between isogenic human kidney organoids expressing wild-type APOL1 (G0) or risk variant APOL1 (G2), which are affected by the levels of APOL1 expression. They also demonstrate that inhibition of diacylglycerol O-acyltransferase 2 (DGAT2), a key enzyme in triglyceride biosynthesis, upregulates genes involved in lipid droplet formation. DGAT2 inhibitors may thus represent a potential therapeutic approach to reduce the cytotoxic effects of APOL1 risk variants that contribute to APOL1 nephropathy. Visual Abstract: Abstract : Background: Two variants in the gene encoding apolipoprotein L1 (APOL1) that are highly associated with African ancestry are major contributors to the large racial disparity in rates of human kidney disease. We previously demonstrated that recruitment of APOL1 risk variants G1 and G2 from the endoplasmic reticulum to lipid droplets leads to reduced APOL1-mediated cytotoxicity in human podocytes. Methods: We used CRISPR-Cas9 gene editing of induced pluripotent stem cells to develop human-derived APOL1 G0/G0 and APOL1 G2/G2 kidney organoids on an isogenic background, and performed bulk RNA sequencing of organoids before and after treatment with IFN- γ . We examined the number and distribution of lipid droplets in response to treatment with inhibitors of diacylglycerol O-acyltransferases 1 and 2 (DGAT1 and DGAT2) in kidney cells and organoids. Results: APOL1 was highly upregulated in response to IFN- γ in human kidney organoids, with greater increases in organoids of high-risk G1 and G2 genotypes compared with wild-type (G0) organoids. RNA sequencing of organoids revealed that high-risk APOL1 G2/G2 organoids exhibited downregulation of a number of genes involved in lipogenesis and lipid droplet biogenesis, as well as upregulation of genes involved in fatty acid oxidation. There were fewer lipid droplets in unstimulated high-risk APOL1 G2/G2 kidney organoids than in wild-type APOL1 G0/G0 organoids. Whereas DGAT1 inhibition reduced kidney organoid lipid droplet number, DGAT2 inhibition unexpectedly increased organoid lipid droplet number. DGAT2 inhibition promoted the recruitment of APOL1 to lipid droplets, with associated reduction in cytotoxicity. Conclusions: Lipogenesis and lipid droplet formation are important modulators of APOL1-associated cytotoxicity. Inhibition of DGAT2 may offer a potential therapeutic strategy to attenuate cytotoxic effects of APOL1 risk variants.